THE DYNAMICS OF LANGUAGE IMMERSION MODELS IN THE I'DAD LUGHAH PROGRAM: ANALYSIS OF STRATEGIES AND CHALLENGES AT STAI AS-SUNNAH DELI SERDANG - Ade Muhammad Ritonga; Tulus Musthofa; Ahmad Zaky (Al-Muyassar: Journal of Arabic Education, 2026)
Research on Arabic language immersion has predominantly focused on learning effectiveness within classroom contexts, while studies that integrate social, institutional, and implementation dynamics in residential-based educational settings remain limited. Therefore, this study aims to analyze the dynamics of the language immersion model in the I’dad Lughah Program at STAI As-Sunnah Deli Serdang, as well as to identify its implementation strategies and the challenges encountered in practice. This research employs a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation, and were analyzed using a descriptive-analytical approach.The findings reveal that the language immersion model is not merely implemented as a pedagogical approach but as an ecological system that integrates formal learning and social practice through a language environment (bi’ah lughawiyah). The implementation strategies include the use of Arabic as the medium of instruction, an immersion-based curriculum, the presence of native speakers, and structured language activities. However, its effectiveness is influenced by several challenges, such as limited use of technology, restrictions on digital access, inconsistent use of Arabic among students, and the heterogeneity of students’ initial language proficiency.These findings offer a conceptual contribution by extending the language immersion model from a classroom-based approach to an ecosystem-based model that emphasizes the interaction between environment, institutional regulation, and social practice. Theoretically, this study enriches the global discourse on language immersion by highlighting the importance of integrating social and institutional dimensions in second language acquisition. Practically, it recommends strengthening adaptive immersion strategies, including the optimization of technology use and differentiated instruction, in order to enhance the effectiveness of Arabic language learning in residential higher education contexts.